Ternary PtFeCu alloys loaded on three-dimensional porous carbon for alkaline hydrogen evolution reaction - Jinlong He; Shuhua Zhao; Siyu Shang; Chenxi Zhou; Deying Wen (Physics Open, 2025)
Ternary PtFeCu alloy nanoparticles were decorated on three-dimensional porous carbon (PtFeCu-3DC) via a self-templating strategy. Benefiting from the synergetic effect of three-dimensional porous carbon and the anchored PtFeCu alloy nanoparticles, could promote the mass transfer efficiency and catalytic activity in alkaline solution. The obtained PtFeCu/3DC-800 catalyst exhibited excellent hydrogen evolution reaction (HER) activity in 1 M KOH with an overpotential as low as 20 mV, a Tafel slope as small as 44.62 mV dec−1, and good durability (50000 s). These results demonstrate the great potential of ternary Pt-based alloys for practical applications.